2019
DOI: 10.1039/c8ta12146j
|View full text |Cite
|
Sign up to set email alerts
|

Hollow polymer dots: nature-mimicking architecture for efficient photocatalytic hydrogen evolution reaction

Abstract: Mimicking nature is always beneficial for improving the performance of artificial systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 57 publications
1
63
0
Order By: Relevance
“…Mimicking a powerhouse cell by reconstitution of the ETC system onto a membrane is not a new idea; it first appeared in 1977. Although the protocol can vary from group to group, the main components are an appropriate interface (formed from lipids, polymers, or hybrids [119] ), a proton pump or photoacid/ photobase generator, [110,114] and ATP synthase. [4a,106a,120] An appropriate interface can be achieved from different building blocks, such as natural and synthetic lipids, three-block copolymers, or hybrid materials.…”
Section: Atp Synthesis In Artificial Cellsmentioning
confidence: 99%
“…Mimicking a powerhouse cell by reconstitution of the ETC system onto a membrane is not a new idea; it first appeared in 1977. Although the protocol can vary from group to group, the main components are an appropriate interface (formed from lipids, polymers, or hybrids [119] ), a proton pump or photoacid/ photobase generator, [110,114] and ATP synthase. [4a,106a,120] An appropriate interface can be achieved from different building blocks, such as natural and synthetic lipids, three-block copolymers, or hybrid materials.…”
Section: Atp Synthesis In Artificial Cellsmentioning
confidence: 99%
“…Increasing the photocatalyst surface area by processing bulk semiconductors into NPs or nanofibers is a simple and commonly employed strategy to increase their EQE. [9,244,245,264,[275][276][277][278][279] Other strategies include designing porous semiconductors such as conjugated microporous polymers and covalent-organic frameworks (COFs) which can allow ingress of hole or electron scavengers into the semiconductor pores. [8,[280][281][282] If the photocatalyst needs to operate in a liquid matrix, efficient wetting of the pores by the solvent/scavenger solution is essential to maximize efficiency.…”
Section: Bulk Heterojunctions In Photocatalytic Applicationsmentioning
confidence: 99%
“…However, these Pdots appeared to be stable for a maximum of 4 h with high roll‐off efficiency. Surprisingly, the same groups reported hollow structured Pdots prepared using conjugated polymer PFODTBT and 8‐hydroxypyrene‐1,3,6‐trisulfonic acid trisodium salt (HTPS) as the copolymer instead of PS−PEG−COOH for hydrogen evolution . Notably, the photocatalysis enhancement mainly depended on the decrease in particle size from 90 to 5 nm.…”
Section: Conjugated Polymer Dots (Pdots)mentioning
confidence: 99%
“…Surprisingly, the same groups reported hollow structured Pdots prepared using conjugated polymer PFODTBT and 8-hydroxypyrene-1,3,6-trisulfonic acid trisodium salt (HTPS) as the copolymer instead of PSÀ PEGÀ COOH for hydrogen evolution. [92] Notably, the photocatalysis enhancement mainly depended on the decrease in particle size from 90 to 5 nm. Overall, this work revealed that nature-mimicking hollow Pdots with porous shells could be ideal photocatalysts applicable in solar energy conversion and storage systems.…”
Section: General Synthesis Of Pdotsmentioning
confidence: 99%